Diseño de un catálogo que recoja la gráfica popular de carteles comerciales de los cantones Salcedo y Pijilí. - Plasencia Santafé, Martha Isabel (2018)
The popular commercial graphics is a form of publicity and its manifests as labeling system elaborated manually with different techniques and materials. These graphics permit to know each commercial establishment. Through these graphics the city is recognized, in the streets of Salcedo and Pujili there are images, illustrations, typographies and colors that serve for recognize typical activities of the shops, feelings, emotions and even personal characters of the merchants (nicknames, surnames, names, diminutives, etc.). Currently, the posters, billboards, flyers and the others graphic resources are produced by technology that are updating; however, there are still graphics that have been created manually so that through their shape, color and style transmit information from smalls shops, such up: vulcanizes, mechanics, stores, pharmacies, ice cream shops, bakeries, bookstores and others. These labels are produced manually and by people who work from the professional design until people with creativity and initiative and innate skills. Or the graphs are elaborated by the merchant himself, initiative motivated by need the promotion a small business and to obtain an economic income. The objective of this project is to design a catalog that collects part of the manual graphics of the commercial establishments of the cantons of Salcedo and Pujili, as well as to describe the graphs through the study of the visual language, to including information about the support and compositional elements of the graphics. In addition, the interviews carried out to three labelings determined the appropriate information about the elaboration and the constructive particularities of the design of the manual advertising, represented in commercial labels. The set design collects and classifies the graphics, taking into account that a catalog is a medium printed that allows to display original and ordered content thanks to its editorial characteristics and policies. In addition, the photograph included in its content facilities the exposure of images of the commercial labels.